Code clone detection model: a SWOT analysis perspective - Mubarak-Ali, Al-Fahim; Rahiwan Nazar, Romli; Nilam Nur, Amir Sjarif (American Scientific Publisher, 2018)
Code clone is similar source code that occurs in a program. Code clone affects the maintainability of software. Therefore, various code clone detection techniquees such as text based comparison technique, token based comparison technique, tree based comparison technique, metric based comparison technique and graph based comparison technique have been proposed to detect code clone. Apart from these techniquees, models also have been used to detect code clone. Model consist of step by step process that is utilized to detect code clones. This work looks into analyzing existing code clone detection models through SWOT analysis. The strength and weakness of these code clone detection models is discussed. The output of this work shows that code clone detection is a more procedural way of detecting code clone through process and the opportunity of expanding the research area is vast.